2023
DOI: 10.18203/2320-6012.ijrms20232418
|View full text |Cite
|
Sign up to set email alerts
|

Study on health seeking behaviour of elderly population for chronic diseases in a rural area of northern Kerala

Abstract: Background: The existing global and national demographic structure is evolving towards a greater number of elderly people. Chronic diseases have negative personal, societal, and financial consequences in all communities and economies. Health seeking behaviour is thought to be the result of a complicated interplay between the patient's disease condition and socioeconomic and demographic variables, as well as the quality, availability, and accessibility of healthcare services. Methods: Community based cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Consistently with most study ndings [25,26,27,28], this study ndings have shown that the married and widowed/divorced elderlies were more likely to seek for healthcare services when they get sick compared to the elderlies who never married before. [29] also found that non-married individuals were more likely to skip medical visitations compared to the married ones.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently with most study ndings [25,26,27,28], this study ndings have shown that the married and widowed/divorced elderlies were more likely to seek for healthcare services when they get sick compared to the elderlies who never married before. [29] also found that non-married individuals were more likely to skip medical visitations compared to the married ones.…”
Section: Discussionsupporting
confidence: 90%